NILAI PESSE: SEBUAH MODEL UNTUK MEMBANGUN KARAKTER ANAK DI SEKOLAH - Lebba Lebba (Universitas Hasanuddin, 2022)
This study aims to explain the inheritance of pesse' value ​​as a model of empathy in building the character of students at schools. After the revitalization of local wisdom has been carried out, it will then reduce the cultural characteristics between generations. In the inheritance of